Solid-Liquid Phase Diagram of the Dimethyl + Dipropyl Adipates System: Application to Low-Temperature Thermal Energy Storage - Sequeira, Maria C. M.; Nikitin, Timur; Caetano, Fernando J. P.; Diogo, Herminio P.; Fareleira, Joao M. N. A.; FAUSTO, RUI (Springer/Plenum Publishers, 2025)
The present study is the continuation of our research work on di-n-alkyl adipates and their potential as phase change materials (PCM) for low-temperature thermal energy storage (TES). The solid-liquid phase diagram for the binary system composed of dimethyl adipate (DMA) and dipropyl adipate (DPA) is presented and analysed. In a previous study, we explored a particular binary system of n-alkyl adipates, namely diethyl and dibutyl adipates, and demonstrated that these compounds possess underappreciated potential as PCMs at sub-zero temperatures. The goal of the current work is to expand on this research by contributing new phase equilibrium data and deepening our understanding of the fundamental thermodynamics governing low-temperature phase behaviour in di-n-alkyl-adipates. The phase diagram for the DMA + DPA binary system was obtained using three complementary techniques: differential scanning calorimetry (DSC), hot-stage microscopy (HSM), and Raman spectroscopy. DSC analysis of sixteen compositions, including the two pure compounds, provided both the temperature and enthalpy values for the solid-liquid and solid-solid phase transitions. The binary system displays eutectic behaviour at low temperatures, with the eutectic point found at 252.83 K and a composition of approximately xDPA = 0.77. Raman spectroscopy confirmed that the system is characterized by a non-isomorphic eutectic phase diagram, indicating differences in the crystal structures of the solid phases. The liquidus line of the binary phase diagram was successfully described using a suitable fitting equation, yielding a root mean square deviation of 0.65 K, indicating excellent agreement between the experimental data and the theoretical model. This fitting also allowed an accurate prediction of the eutectic composition and temperature. A Tammann diagram is also presented, further confirming the eutectic composition and associated enthalpy. This work addresses a gap in the literature by presenting, for the first time, the solid-liquid phase equilibrium behaviour of the DMA + DPA binary system (including the detailed solid-liquid phase diagram of the system). The findings provide valuable insight into the potential use of this system as PCM for sub-zero TES applications, supporting their consideration in future thermal energy storage technologies.
Keywords: Adipates; Eutectic; Low-temperature Energy Storage (TES); Phase Change Material (PCM); Solid–liquid Phase Diagram